2018
DOI: 10.1111/bjhp.12321
|View full text |Cite
|
Sign up to set email alerts
|

An examination of accuracy and bias in perceptions of a partner's motives for health behaviour regulation

Abstract: Although people are somewhat accurate in their perceptions of their romantic partner's motives for attempting to influence their health behaviours, their perceptions are also contaminated by biases. This suggests that people's judgements about their partner's motives could be substantially improved. Statement of contribution What is known about this subject? Romantic partners use social influence tactics to improve each other's health behaviours. People who perceive their partner's influence attempts positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…1Data used in Study 1 has been used in another publication (Berzins, LaBuda, & Gere, 2018) that does not use any daily diary data and focuses on people’s long-term and short-term motives toward their own health. Thus, there is no overlap in the data used for the studies and the topic of the published study is health motives.…”
mentioning
confidence: 99%
“…1Data used in Study 1 has been used in another publication (Berzins, LaBuda, & Gere, 2018) that does not use any daily diary data and focuses on people’s long-term and short-term motives toward their own health. Thus, there is no overlap in the data used for the studies and the topic of the published study is health motives.…”
mentioning
confidence: 99%
“…Being married was associated with seeking healthcare earlier than being unmarried. While beyond the scope of our study, previous studies have shown that partners of patients may directly or indirectly encourage earlier healthcare-seeking in the United States, 18 Tanzania, Malawi and South Africa. 19 The influence of partners may represent an opportunity for health systems to engage patients and their significant others in promoting timely visits to health centres.…”
Section: Discussionmentioning
confidence: 99%
“…Potential participants were recruited through flyers posted on campus, email announcements, listings via the school's subject pool system as well as through snowball sampling. We followed recent research that used Truth and Bias models and looked to recruit a minimum of 100 couples (e.g., Berzins et al., 2018; Finkel et al, 2015, Spielmann et al., 2020). Participants received detailed information about the study, completed IRB‐approved informed consent, as well as the PPDC scale and measures of perceived partner commitment, attachment anxiety and own dissolution consideration among others.…”
Section: Methodsmentioning
confidence: 99%
“…Truth and Bias model approach (West & Kenny, 2011) to examine these questions. couples (e.g., Berzins et al, 2018;Finkel et al, 2015, Spielmann et al, 2020. Participants received detailed information about the study, completed IRB-approved informed consent, as well as the PPDC scale and measures of perceived partner commitment, attachment anxiety and own dissolution consideration among others.…”
Section: Studymentioning
confidence: 99%